2008
DOI: 10.1111/j.1365-2648.2007.04528.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluid compliance among patients having haemodialysis: can an educational programme make a difference?

Abstract: Nephrology nurses often have long-term relationships with their patients and are ideally placed to provide ongoing education and encouragement, especially for those experiencing difficulties in adhering to fluid and dietary restrictions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
1
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 20 publications
4
53
1
5
Order By: Relevance
“…In line with our findings, most previous studies showed the positive effects of education on weight management (38), itching, and nausea (25,39,40). Nonetheless, a study reported that education did not significantly affect fluid intake and was not effective in behavior modification (41).…”
Section: Discussionsupporting
confidence: 82%
“…In line with our findings, most previous studies showed the positive effects of education on weight management (38), itching, and nausea (25,39,40). Nonetheless, a study reported that education did not significantly affect fluid intake and was not effective in behavior modification (41).…”
Section: Discussionsupporting
confidence: 82%
“…Self-report and intradialytic weight gain were used to measure fluid adherence in CKD participants. Non adherence using inter-dialytic weight gain ranged from 9.7% in USA to 70% in UK (24,35,36,37,38,39,40,41,42,43,44). Through self-report, non-adherence to fluid intake ranged from 40.3% in China to 72% in Belgium (19,45).…”
Section: Medication Adherencementioning
confidence: 99%
“…(1) IDWG as a measure of nonadherence: For decades it has been emphasized that adherence to fluid restriction is necessary to reduce IDWG, and IDWG has been equated with nonadherence [28,29,30,31,32,33,34,35,36,37,38] (in an oversimplified disregard of the thirst mechanism, as specified below).…”
Section: Interdialytic Weight Gain: Reported Causes and Consequencesmentioning
confidence: 99%